2022
DOI: 10.3389/fpls.2022.812988
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of WRKY Resistance Gene Family in Boehmeria nivea (L.) Gaudich: Crosstalk Mechanisms of Secondary Cell Wall Thickening and Cadmium Stress

Abstract: A total of 60 WRKY family genes of ramie were identified in the ramie. The genes were unevenly distributed across 14 chromosomes in the specie and highly concentrated (72%) in the distal telomeric region. Phylogenetic analysis placed these genes into seven distinct subfamilies groups: I, II (a, b, c, d, e), and III, with group IIc containing only the variant of heptapetide sequence (WRKYGKK). Segmental duplication events (41.7%) was found to be the main driver of BnGWRKY evolution. Thirty eight from among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Investigating the expression patterns of genes in various tissues is of paramount importance for mining functional genes ( Dutta et al., 2018 ). Research has demonstrated that WRKY genes exhibit expression in one or more tissues, and they are crucial for plant growth and development ( Feng et al., 2022 ; Zhang et al., 2022b ). The evolutionary relationship between CsWRKY7 and AtWRKY7 in Camellia sinensis is closely related, and root elongation was higher in CsWRKY7 than in wild type ( Chen et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the expression patterns of genes in various tissues is of paramount importance for mining functional genes ( Dutta et al., 2018 ). Research has demonstrated that WRKY genes exhibit expression in one or more tissues, and they are crucial for plant growth and development ( Feng et al., 2022 ; Zhang et al., 2022b ). The evolutionary relationship between CsWRKY7 and AtWRKY7 in Camellia sinensis is closely related, and root elongation was higher in CsWRKY7 than in wild type ( Chen et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…WRKY genes play an important role in cell wall synthesis. WRKY genes are a family of transcription factors that regulate various plant processes, including stress responses, development, and secondary metabolism ( Wang et al., 2010 ; Feng et al., 2022 ). WRKY genes can affect secondary cell wall thickening by binding to the promoters of other transcription factors that activate secondary wall synthesis ( Wang et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ramie and Arabidopsis have 11 ortholog gene pairs, against 6 between the former and rice. These conserved genes might have similar functions across different species [51]. Because gene duplication is crucial in the evolution process, gene functions, and plant diversity [52], we investigated the presence of segmental and tandem duplications in the orthologues gene pairs (Table S5).…”
Section: Gene Duplications and Synteny Analysismentioning
confidence: 99%
“…The rate of the nonsynonymous (Ka) and synonymous (Ks) substitutions among the segmentally duplicated pairs ranged from 0.0361 (BnWOX10/14) to 1.6615 (BnWOX6A/ Maker00021031). The substitution rates were defined as Ka/Ks >1 (positive or diversifying selection), <1 (negative or purifying selection), and Ka/Ks = 1 as neutral mutation [51]. From the result (Table S5), we can deduce that all the duplicated genes have undergone purifying selection within the WOX family, except for BnWOX6A and its homolog that went through diversifying selection, which may be expected, as the homolog is not a WOX gene.…”
Section: Gene Duplications and Synteny Analysismentioning
confidence: 99%